2019 IEEE International Symposium on Information Theory (ISIT) 2019
DOI: 10.1109/isit.2019.8849277
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Adaptive Recoding Framework for Batched Network Coding

Abstract: Batched network coding is a variation of random linear network coding which has low computational and storage costs. In order to adapt random fluctuations in the number of erasures in individual batches, it is not optimal to recode and transmit the same number of packets for all batches. Different distributed optimization models, which are called adaptive recoding schemes, were formulated for this purpose.The key component of these optimization problems is the expected value of the rank distribution of a batch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The above two models of adaptive recoding schemes were unified in Reference [ 82 ] when the expected rank functions are concave with respect to t . The unified model is similar to the one in Reference [ 44 ] but it becomes a concave optimization problem by performing linear interpolations on the discrete expected rank functions.…”
Section: Recoding Schemesmentioning
confidence: 99%
See 4 more Smart Citations
“…The above two models of adaptive recoding schemes were unified in Reference [ 82 ] when the expected rank functions are concave with respect to t . The unified model is similar to the one in Reference [ 44 ] but it becomes a concave optimization problem by performing linear interpolations on the discrete expected rank functions.…”
Section: Recoding Schemesmentioning
confidence: 99%
“…Regarding the optimal solution, Reference [ 82 ] showed that there is a robust solution which can tolerate inaccuracy on the input rank distribution. Also, there is a robust solution where the number of recoded packets is almost deterministic , that is, there is at most one rank such that the batches of this rank have a choice to transmit one more recoded packet.…”
Section: Recoding Schemesmentioning
confidence: 99%
See 3 more Smart Citations